2020
DOI: 10.1371/journal.pone.0236917
|View full text |Cite
|
Sign up to set email alerts
|

Public perspectives on protective measures during the COVID-19 pandemic in the Netherlands, Germany and Italy: A survey study

Abstract: Background The extent to which people implement government-issued protective measures is critical in preventing further spread of coronavirus disease 2019 (COVID-19) caused by coronavirus SARS-CoV-2. Our study aimed to describe the public belief in the effectiveness of protective measures, the reported implementation of these measures, and to identify communication channels used to acquire information on COVID-19 in European countries during the early stage of the pandemic. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 33 publications
8
88
0
7
Order By: Relevance
“…Our results are similar to another study [ 15 ]. Meier et al also reported that television, newspapers, official health websites, and SM were the most frequently used information sources [ 16 ]. SM has extensive “health misinformation," often described as information that contradicts existing evidence from medical specialists [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are similar to another study [ 15 ]. Meier et al also reported that television, newspapers, official health websites, and SM were the most frequently used information sources [ 16 ]. SM has extensive “health misinformation," often described as information that contradicts existing evidence from medical specialists [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practice score ranged from 0 to 12 (yes = 2 points, sometimes = 1, and no = 0), and a score of ďż˝6 was considered adequate while <6 was considered inadequate. The misconception questions score ranged from 1 to 19 (correct [true] answer = 1 score, wrong [false] answer = 0 score, not sure = 0 score) and scores ďż˝50% (1-9) were considered to be poor concepts, and individuals with a >50% score (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) were considered high scorers, indicated good concepts.…”
Section: Introductionmentioning
confidence: 99%
“…The measures taken by the German government were largely accepted by the population, the number of cases declined steadily and stayed low during the summer months ( Figure 3 ). Other factors likely to have contributed include an intense broad and science-oriented information and discussion of national and international epidemic developments in the German media, and an active and unified political leadership [ 55 ]. The warm and dry weather during summer, which allowed for outdoor social activities, probably contributed to keeping case load low [ 16 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…This example indicates the role of political and social context in the success of a PHI [30]. Effectiveness of a non-pharmaceutical PHI is tailored to changing the behavior of the target population [31,32]. That is, if people change their behavior in a way to follow preventive measures in COVID-19 pandemics, the spread of the disease will slow down; and at this regard, there are some theories that explain the behavior change mechanism in the real world.…”
Section: Context In Phismentioning
confidence: 99%